Lifelines of our society a global history of infrastructure - Laak, Dirk van 1961- (The MIT Press, 2023)
"A global history of modern infrastructures covering two centuries of historical dynamics from all over the world"--
Keywords: Geschichte; Geschichte 1800-2000; Moderne; Technischer Fortschritt; Alltag; Infrastruktur; Infrastructure (Economics) / History